2006
DOI: 10.1179/136485906x86220
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the therapeutic efficacy of chloroquine for the treatment of uncomplicated,Plasmodium falciparummalaria in Iran

Abstract: Between 2002 and 2004, the standardized 28-day protocol recently developed by the World Health Organization was used to explore the efficacy of chloroquine, in the treatment of uncomplicated, Plasmodium falciparum malaria, in five sentinel sites in southern Iran. All but 14 of the 158 patients enrolled (128, 28 and two from the provinces of Sistan-Baluchestan, Hormozgan and Kerman, respectively) were successfully followed-up. The overall frequency of treatment failure by day 28 was 78.5%, with 17.4% of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…The high prevalence of CQ treatment failure by D28 (78.5%) in south-eastern province of Iran was also reported in another study. 6 Therefore, the present data suggest that these 4 mutations in the pfcrt gene might have been selected by treatment and therefore can be used as molecular markers to monitor CQR in this region of the world.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The high prevalence of CQ treatment failure by D28 (78.5%) in south-eastern province of Iran was also reported in another study. 6 Therefore, the present data suggest that these 4 mutations in the pfcrt gene might have been selected by treatment and therefore can be used as molecular markers to monitor CQR in this region of the world.…”
Section: Discussionmentioning
confidence: 68%
“…An in vivo study carried out by Raeisi and co-workers during 2002-2004 also showed that the frequency of treatment failure by day 28 was 78.5% in south-eastern provinces of Iran. 6 Although resistance to CQ has been well documented, this anti-malarial drug is still used as the standard treatment of uncomplicated malaria in many geographic regions. Some progress has been made in understanding the mechanism of action of CQ, but it has not yet been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, the burden of malaria has declined gradually from 96, 340 in 1991 to 15,712 total cases in 2007, and further reduction was reported in 2013, with total cases of 1,373 due to the scaling-up of different interventions (CDMC, Tehran, Iran, unpublished data). Resistance to CQ was reported in Sistan and Baluchistan Province in 1983 (Edrissian et al, 1986), and this resistance was increased to more than 78.5% of treatment failures in this area (Raeisi et al, 2006). As the intensity of CQ resistance increased, in 2005, the country changed the CQ, as first-line antimalarial treatment, to a combination of SP-CQ and artemetherlumefantrine (CoArtem Ò ), as the second-line drug (Zakeri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During the last six years, 15000 to 25000 cases have been reported each year in Iran and more than 85% of them occurred in the south and southeast of Iran (Department of communicable Disease Control). The current annual parasite index (API) is 7 per 1000 inhabitants in the endemic area [5]. Several factors, such as presence of insecticide resistance among vectors [6], parasite drug resistance [7], and socioeconomical problems and population movement [5, 8], have made eradication in this area so difficult.…”
Section: Introductionmentioning
confidence: 99%